Town planning in theory and practice. A report of a conference arranged by the Garden city association, held [...], London, on Oct. 25th, 1907 [...], Papers and speeches by [J.S.] Nettlefold, A. Williams, Prof. P. Geddes a.o (London, 1907)
With plans.